The Provincial Nominee Program: Retention in province of landing - Garnett Picot; Eden Crossman; Feng Hou (Economic and Social Reports)
The Provincial Nominee Program (PNP) is designed to contribute to a more equitable distribution of new immigrants across Canada. A related objective is the retention and integration of provincial nominees in the nominating province or territory. This article is the second in a series that examines the characteristics and labour market outcomes of PNP immigrants and examines the retention of PNP immigrants at both the national and provincial or territorial levels. The analysis uses data from the Immigrant Landing File and tax records, along with three indicators of retention, to measure the propensity of a province or territory to retain immigrants.